The contralateral hip in slipped capital femoral epiphysis: Is there an easy-to-use algorithm to support a decision for prophylactic fixation? - Lindell, Mikael; Sköldberg, Martin; Stenmarker, Margaretha; Michno, Piotr; Herngren, Bengt (Journal of children's orthopaedics, 2022)
Purpose: To identify a specific factor that can support the decision for prophylactic fixation in unilateral slipped capital femoral epiphysis. Methods: This retrospective cohort study included a total national population of 379 children diagnosed with slipped capital femoral epiphysis from 2007 to 2013. Regression analysis used information on slip severity, clinical classification of the index hip, age, sex, age-adjusted body mass index, the difference in epiphyseal–diaphyseal angle, and comorbidity to identify any risk factor for the subsequent development of a slip in the contralateral hip. Four observers evaluated the triradiate cartilage following the modified Oxford bone score grade. The occurrence of later development of a contralateral slip in different stage of physeal closure was used to analyze the sensitivity and specificity for this method. Results: This study’s only predictor for a subsequent contralateral slip was chronological age. At age 13 years or older, 1/15 in girls and 3/65 in boys suffered from a slip in the contralateral hip. Thus, when using age <13 years as a test for deciding when to do prophylactic fixation, the sensitivity would be 88% and specificity 51% for preventing contralateral slip. However, the correlation between the four different observers was too low to be considered useful when assessing the triradiate cartilage for skeletal maturity. Conclusion: We would advocate a prophylactic fixation for children <13 years diagnosed with a unilateral slipped capital femoral epiphysis as an easy-to-use algorithm. Level of evidence: level II.